Admission [videorecording (DVD)] - Weitz, Paul, 1966-; Fey, Tina, 1970-; Rudd, Paul; Sheen, Michael; Tomlin, Lily; Shawn, Wallace; Korelitz, Jean Hanff, 1961- (Universal Studios Home Entertainment, 2013)
A Princeton admissions officer, Portia Nathan, who is up for a major promotion, takes a professional risk after she meets a college-bound alternative school kid who just might be the son she gave up years ago in a secret adoption.